Description of the immatures of Linepithema humile Mayr (Hymenoptera: Formicidae) - Solis, Daniel R. [UNESP]; Fox, Eduardo G. P. [UNESP]; Rossi, Mônica L.; Bueno, Odair C. [UNESP] (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2010)
Linepithema humile Mayr is an ant species originally native to South America that has been spread accidently throughout the globe through international trade. It is a serious urban and crop pest. Despite its economic importance, little is known about the larvae of this species apart from a brief description based on a few specimens. The present investigation is aimed at describing every immature stage of L. humile. Three larval instars were determined through the frequency distribution of the maximum width of head capsules from a sample of 525 larvae. The morphological descriptions were based on 150 eggs, 70 larvae, and 90 pupae examined by light and scanning electron microscopy. Some morphological characteristics reported to be typical of Linepithema Mayr larvae were confirmed - dolichoderoid body shape, presence of dorsal protuberance, sparse simple body hairs, presence of nine pairs of spiracles and dolichoderoid mandibles. We concluded that an earlier published description was based on queen larvae, and that the protuberance is only present in worker larvae. The information provided in this study may aid ant systematics and phylogenetics, as well provide a better understanding of the biology of this species.
Keywords: Argentine ant; Dolichoderinae; Dolichoderini; Iridomyrmex humilis; Larval instars; Tramp species